Endoscopic Optical Coherence Tomography for Evaluation of Success of Tympanoplasty. Issue 7 (August 2020) - Morgenstern, Joseph; Schindler, Martin; Kirsten, Lars; Golde, Jonas; Bornitz, Matthias; Kemper, Max; Koch, Edmund; Zahnert, Thomas; Neudert, Marcus
Abstract : Objective: After tympanoplasty, it is often challenging to differentiate between different causes of a remaining air bone gap (ABG). Optical coherence tomography (OCT) offers a new approach for combined morphologic and functional measurements of the tympanic membrane and adjacent parts of the middle ear. Thus, it provides valuable diagnostic information in patients with a reduced sound transfer after middle ear surgery. Patient and intervention: A patient with history of tympanoplasty and a persistent ABG was investigated with endoscopic OCT before revision surgery. Main Outcome Measures: The oscillation behavior and the thickness of the reconstructed tympanic membrane was determined. The oscillation amplitudes of the inserted prosthesis were compared to a finite element model simulation and to the clinical findings and the audiometric data of the patient. Results: OCT measurements showed a reduced oscillation amplitude of the prosthesis while revealing an aerated middle ear and good coupling of the prosthesis. Transfer loss measured by OCT showed a similar progression as the ABG measured by pure-tone audiometry with a mean divergence of 4.45 dB. Conclusion: Endoscopic OCT is a promising tool for the evaluation of tympanoplasty outcome. It supports established otologic diagnostics and can help differentiating between different causes of conductional hearing loss. Abstract : Supplemental Digital Content is available in the text